Sand fly saliva: effects on host immune response and Leishmania transmission - Rohousová, Iva; Volf, Petr (Folia parasitologica, 2006)
The feeding success of sand flies (Diptera: Phlebotominae) is linked to the vast array of pharmacological substances in their saliva, which interferes with the host haemostasis and immune response. Modification of feeding site plays also an important role in Leishmania transmission. In naive hosts, co-inoculation of saliva and Leishmania parasites increases the chance of successful transmission. Disease exacerbation seems to be associated with enhanced production of type 2 cytokines and selective inhibition of some macrophage functions including the production of NO and H202. On the other hand, hosts repeatedly exposed to sand fly bites develop anti-saliva immune response that results in a protection against Leishmania infection. This led to a new interesting approach to anti-Leishmania vaccine--using salivary components to block parasite transmission. The review is therefore focused on the interactions that run between immunomodulatory molecules in sand fly saliva and host immune response, with the impact on Leishmania infection development. Recent studies revealed that saliva-based vaccine for leishmaniasis might be effective and feasible, however, several questions still require to be solved. The knowledge based on experimental mouse model cannot be fully extrapolated to dogs or humans and due to differences in salivary antigens between sand fly species the protective effect is species-specific. On the other hand, the specificity of salivary antigens enables the use of anti-saliva antibodies for monitoring the exposure of hosts to sand fly bites and might be used as a marker of risks for Leishmania transmission in endemic areas.
Keywords: Leishmaniasis; Animals; přenos infekční nemoci; leishmanióza; hmyz - vektory; zvířata; Saliva; Disease Transmission, Infectious; Insect Vectors; Leishmania; Psychodidae; sliny